Linking salinity stress tolerance with tissue-specific Na+ sequestration in wheat roots - Wu, Honghong; Shabala, Lana; Liu, Xiaohui; Azzarello, Elisa; Zhou, Meixue; Pandolfi, Camilla; Chen, Zhong-Hua; Bose, Jayakumar; Mancuso, Stefano; Shabala, Sergey (Frontiers in Plant Science, 2015)
Salinity stress tolerance is a physiologically complex trait that is conferred by the large array of interacting mechanisms. Among these, vacuolar Na+ sequestration has always been considered as one of the key components differentiating between sensitive and tolerant species and genotypes. However, vacuolar Na+ sequestration has been rarely considered in the context of the tissue-specific expression and regulation of appropriate transporters contributing to Na+ removal from the cytosol. In this work, six bread wheat varieties contrasting in their salinity tolerance (three tolerant and three sensitive) were used to understand the essentiality of vacuolar Na+ sequestration between functionally different root tissues, and link it with the overall salinity stress tolerance in this species. Roots of 4-day old wheat seedlings were treated with 100 mM NaCl for 3 days, and then Na+ distribution between cytosol and vacuole was quantified by CoroNa Green fluorescent dye imaging. Our major observations were as follows: (1) salinity stress tolerance correlated positively with vacuolar Na+ sequestration ability in the mature root zone but not in the root apex; (2) contrary to expectations, cytosolic Na+ levels in root meristem were significantly higher in salt tolerant than sensitive group, while vacuolar Na+ levels showed an opposite trend. These results are interpreted as meristem cells playing a role of the “salt sensor;” (3) no significant difference in the vacuolar Na+ sequestration ability was found between sensitive and tolerant groups in either transition or elongation zones; (4) the overall Na+ accumulation was highest in the elongation zone, suggesting its role in osmotic adjustment and turgor maintenance required to drive root expansion growth. Overall, the reported results suggest high tissue-specificity of Na+ uptake, signaling, and sequestration in wheat roots. The implications of these findings for plant breeding for salinity stress tolerance are discussed.